1970
DOI: 10.1002/ijc.2910050315
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical study on rat liver glycogen during dab carcinogenesis

Abstract: Section of normal rat liver stained with toluidine blue. RNA staining is slightly more intense in cells around portal spaces (ps) than around the central veins (cv). x93. FIGURE 2Adjacent section stained by the PAS reaction. Glycogen staining is slightly more intense in centrolobular areas than in periportal areas. x 93. FIGURE 3Liver section from a rat fed DAB for 30 days. Toluidine blue staining reveals a loss of RNA in centrolobular areas (delimited by broken lines). ~9 3 . FIGURE 4Adjacent section stained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…From the sequence of cellular changes observed during hepatocarcinogenesis in the rat liver we concluded that the clear and acidophilic glycogen storage cells persisting after withdrawal of the carcinogen represent a preneoplastic cell population, the neoplastic transformation of which is accompanied by a gradual reduction of the glycogen and a concomitant increase in ribosomes (4,10). The findings of many other authors (31,33,79,84,100 and others) and recent results of enzyme-histochemical investigations (38) are in agreement with this concept. Further support is given by observations in mice treated with various hepatocarcinogens (12,47,65,77,104) and results obtained in some other species, such as Mastomys (106) and monkeys (76).…”
Section: Sequential Cellular Changes During Hepatocarcinogenesis In Ssupporting
confidence: 81%
“…From the sequence of cellular changes observed during hepatocarcinogenesis in the rat liver we concluded that the clear and acidophilic glycogen storage cells persisting after withdrawal of the carcinogen represent a preneoplastic cell population, the neoplastic transformation of which is accompanied by a gradual reduction of the glycogen and a concomitant increase in ribosomes (4,10). The findings of many other authors (31,33,79,84,100 and others) and recent results of enzyme-histochemical investigations (38) are in agreement with this concept. Further support is given by observations in mice treated with various hepatocarcinogens (12,47,65,77,104) and results obtained in some other species, such as Mastomys (106) and monkeys (76).…”
Section: Sequential Cellular Changes During Hepatocarcinogenesis In Ssupporting
confidence: 81%
“…Its content in liver tumor cells varies greatly. Glycogen diminishes during chemical hepatocarcinogenesis and is not present in most fully developed hepatocellular tumors (Bannasch and Muller, 1964;Bannasch, 1968;Edwards and White, 1942;Forget and Danoust, 1970;Laqueur et al, 1963;Schauer and Kunze, 1968;Sydow and Fry, 1969). Glycogen also diminishes in virus-induced avian hepatomas (Lapis, 1979) and human hepatomas Schaff et al, 1971), whereas it is abundant in hepatocellular carcinoma of the tubular or acinar type (Lapis and Johannessen, 1979).…”
Section: Glycogen and Glucose-6-phosphatasementioning
confidence: 99%